2005
DOI: 10.1038/sj.ijo.0802950
|View full text |Cite
|
Sign up to set email alerts
|

Snacking frequency in relation to energy intake and food choices in obese men and women compared to a reference population

Abstract: OBJECTIVE:To investigate snacking frequency in relation to energy intake and food choices, taking physical activity into account, in obese vs reference men and women. DESIGN: Cross-sectional, descriptive study. SUBJECTS: In total, 4259 obese, middle-aged subjects (1891 men and 2368 women) from the baseline examination of the XENDOS study and 1092 subjects (505 men and 587 women) from the SOS reference study were included. MEASUREMENTS: A meal pattern questionnaire describing habitual intake occasions (main mea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
143
6
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 263 publications
(158 citation statements)
references
References 33 publications
(59 reference statements)
8
143
6
1
Order By: Relevance
“…Results showing that the BMI correlated negatively with the daily number of snacks are unexpected; however, there is evidence to suggest that snacking, per se , may not necessarily predispose to overweight (Drummond et al 1996;Berteus-Forslund et al 2005). The explanation for such a correlation found in this study may lie in a result previously published where fruit was shown to be first choice for snacks in Croatian university students (Colić Barić et al 2003).…”
Section: Discussioncontrasting
confidence: 37%
“…Results showing that the BMI correlated negatively with the daily number of snacks are unexpected; however, there is evidence to suggest that snacking, per se , may not necessarily predispose to overweight (Drummond et al 1996;Berteus-Forslund et al 2005). The explanation for such a correlation found in this study may lie in a result previously published where fruit was shown to be first choice for snacks in Croatian university students (Colić Barić et al 2003).…”
Section: Discussioncontrasting
confidence: 37%
“…There is a great deal of controversy as to the optimal frequency of eating occasions or even whether it is truly necessary for healthy individuals to eat between meals. Snacking is generally associated with excess calorie consumption, but for some groups it increases the ability to meet guidelines for milk and fruit consumption (Bertéus Forslund, Torgerson et al 2005; Sebastian, Cleveland et al 2008). Given that youth typically consume insufficient fruits and vegetables, these should be preferentially made available, if snacking is necessary.…”
Section: Resultsmentioning
confidence: 99%
“…This finding seems plausible, given the observed positive association between eating frequency and energy intake [67,75,76]. In addition, the authors called attention to the apparent inverse relation between eating frequency and adiposity measures, such as an artifact that in part can be attributed to the underreporting of eating frequency concomitant with the underreporting of energy intake by obese or overweight subjects [74].…”
Section: Eating Frequencymentioning
confidence: 99%